Influence of dietary docosahexaenoic acid in combination with other long-chain polyunsaturated fatty acids on expression of biosynthesis genes and phospholipid fatty acid compositions in tissues of post-smolt Atlantic salmon (Salmo salar) - Betancor, Monica; Howarth, Fraser J E; Glencross, Brett; Tocher, Douglas R (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2014)
To investigate interactions of dietary LC-PUFA, a dose-response study with a range of docosahexaenoic acid (DHA; 22:6n - 3) levels (1 g kg- 1, 5 g kg- 1, 10 g kg- 1, 15 g kg- 1 and 20 g kg- 1) was performed with post-smolts (111 ± 2.6 g; mean ± S.D.) over a nine-week feeding period. Additional diets included 10 g kg- 1 DHA in combination with 10 g kg- 1 of either eicosapentaenoic acid (EPA; 20:5n - 3) or arachidonic acid (ARA; 20:4n - 6), and a diet containing 5 g kg- 1 each of DHA and EPA. The liver, brain, head kidney and gill were collected at the conclusion of the trial, and lipid and fatty acid compositions were determined as well as expression of genes of LC-PUFA biosynthesis. Total lipid content and class composition were largely unaffected by changes in dietary LC-PUFA. However, phospholipid (PL) fatty acid compositions generally reflected that of the diet, although the response varied between tissues. The liver most strongly reflected diet, followed by the head kidney. In both tissues increasing dietary DHA led to significantly increased DHA in PL and inclusion of EPA or ARA led to higher levels of these fatty acids. The brain showed the most conserved composition and gene expression profile, with increased dietary LC-PUFA resulting in only minor changes in PL fatty acids. Dietary LC-PUFA significantly affected the expression of Δ6 and Δ5 desaturases, Elovl 2, 4 and 5, and SREBPs although this varied between tissues with greatest effects observed in the liver followed by the head kidney, similar to PL fatty acid compositions.